Дослідження ефективності використання AI інструментів при проектуванні графічного інтерфейсу користувача - Кравцов, Д. О. (ХНУРЕ, 2024)
This work is dedicated to the investigation and analysis of using AI tools in the field of user interface design. There are various such tools and each has its unique features and potential for enhancing productivity and work quality. Understanding the specifics of each tool and its optimal use can significantly improve the quality of the final product. The aim of this work is not only to compare the effectiveness of AI tools but also to identify the most productive approaches to their use in different scenarios. Through experimental research, time indicators required for performing typical actions by users will be determined, and their effectiveness will be analyzed.
Keywords: графічний інтерфейс; інтерфейс користувача